Sulfone polymer hollow fiber ultrafiltration membrane, preparation method and application thereof, and assembly with ultrafiltration membrane

By adjusting the structural characteristics of the hollow fiber ultrafiltration membrane of sulfone polymers, including the pore density of the outgoing liquid and the pore size ratio of the inlet liquid surface, the problems of insufficient pressure strength and flux of the existing membrane are solved, and the effects of high throughput and high mechanical strength are achieved.

CN119607899AActive Publication Date: 2025-03-14HANGZHOU COBETTER FILTRATION EQUIPMENT CO LTD

Patent Information

Application Number
CN202411926624.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-14
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The surface density of the external liquid of the existing sulfone polymer hollow fiber ultrafiltration membrane is high, resulting in low pressure resistance, low flux and high processing difficulty.

Method used

By regulating the pore density of the outer liquid surface, the pore size ratio of the inner liquid inlet surface to the outer liquid surface, the overall porosity and pore size of the membrane, the overall high throughput and high mechanical strength of the membrane are achieved.

Benefits of technology

The pressure resistance strength of the ultrafiltration membrane and the overall mechanical strength of the membrane are improved, the flux and filtration efficiency are enhanced, and the risk of membrane pollution is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119607899A_ABST
    Figure CN119607899A_ABST
Patent Text Reader

Abstract

The invention provides a sulfone polymer hollow fiber ultrafiltration membrane, a preparation method and application thereof, and an assembly with the ultrafiltration membrane. When the hole density of the outer liquid outlet surface of the sulfone polymer hollow fiber ultrafiltration membrane is small, the membrane overall flux is still good under a specific structure in which the SEM average pore size of the outer liquid outlet surface, the ratio of the SEM average pore size of the inner liquid inlet surface to the SEM average pore size of the outer liquid outlet surface, the overall pore size of the ultrafiltration membrane and the value of the porosity are within a specific range; meanwhile, the effects of excellent compression strength of the liquid level outside the membrane, excellent mechanical strength of the whole membrane and reduction of the risk that the liquid level outside the membrane is polluted are achieved, and further, when the prepared sulfone polymer hollow fiber ultrafiltration membrane is processed into an assembly, membrane filaments have excellent bonding force; the quality and the preparation success rate of the hollow fiber assembly are improved, and biological ultrafiltration under harsh conditions can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of membrane materials, and more specifically to a sulfone polymer hollow fiber ultrafiltration membrane, a preparation method and application thereof, and a component with the ultrafiltration membrane. Background Art

[0002] The biopharmaceutical industry is closely related to life and health, and has always occupied an important position in the national economic development. Since the biopharmaceutical industry's biopharmaceuticals are inseparable from the ultrafiltration process (including clarification filtration, product concentration, heat source removal, small molecule impurity removal, desalination and buffer exchange, etc.), ultrafiltration membranes play a very important role in the development of the biopharmaceutical industry.

[0003] Ultrafiltration membrane is a kind of membrane made of organic high molecular polymers according to a certain process. According to the different types of polymers, polymer ultrafiltration membranes can be subdivided into cellulose polymer ultrafiltration membranes, polyethylene polymer ultrafiltration membranes, polyamide polymer ultrafiltration membranes, sulfone polymer ultrafiltration membranes, etc.; according to the geometric shape of the membrane, they can be divided into plate ultrafiltration membranes (flat ultrafiltration membranes) and hollow fiber ultrafiltration membranes. In particular, hollow fiber ultrafiltration membranes are widely used in the separation and purification of various biomacromolecules because of their advantages such as not easily causing damage to biomacromolecules and good separation effect. In particular, sulfone polymer hollow fiber ultrafiltration membranes have better high temperature resistance and biocompatibility than other polymer hollow fiber ultrafiltration membranes, and are more favored by the ultrafiltration link of biopharmaceuticals.

[0004] In the prior art, many sulfone polymer hollow fiber ultrafiltration membranes are disclosed, which are basically structures with a skin layer on the inner liquid inlet surface and open macropores on the outer liquid surface, that is, the membrane pores on the inner liquid inlet surface are very small in diameter and have a very low pore density, while the membrane pores on the outer liquid surface are very large in diameter and have a high pore density. Such a membrane structure is conducive to the interception of substances at and near the inner liquid inlet surface, and at the same time, the filtration resistance is small and the flux is high, thereby achieving both the retention efficiency and the flux of the ultrafiltration membrane (this is almost the ideal inner and outer liquid inlet and outlet surface structure recognized in the ultrafiltration membrane industry); for example, the membrane structure disclosed in Publication No. CN16847 Chinese Patent No. 27A (applied by Asahi Kasei Medical Corporation) - Plasma Purification Membrane and Plasma Purification System discloses a hollow fiber plasma purification membrane, which is prepared from aromatic polysulfone and polyvinyl pyrrolidone and has a sponge structure, in which the pore size continuously decreases from the outgoing liquid surface of the membrane to the inlet liquid surface, and there are circular or elliptical holes on the outgoing liquid surface, the holes have an average pore size of 1 μm or more (the membrane pores on the outgoing liquid surface are larger), and the porosity of the outgoing liquid surface of the membrane is 10% or more, thereby showing excellent permeability characteristics and classification performance.

[0005] However, after continuous research, it was found that the ultrafiltration of the above-mentioned membrane pore structure also has certain disadvantages; since the holes on the outflowing liquid surface of the ultrafiltration membrane are large and the number of holes is large, it is easy to cause the pressure resistance of the outflowing liquid surface to be low (even causing the overall mechanical strength of the membrane filament to be low). When the outflowing liquid surface of the membrane filament is subjected to external force, the membrane pores are easy to collapse or deform, and the difficulty of processing the membrane filament into a membrane assembly is greatly increased. For example, due to the poor mechanical strength of some membrane filaments, a membrane assembly can only be made by brushing glue on each membrane filament individually, which consumes a lot of manpower and material resources; therefore, there is an urgent need to develop a hollow fiber ultrafiltration membrane with high flux, high pressure resistance of the outflowing liquid surface and high overall mechanical strength of the membrane. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a sulfone polymer hollow fiber ultrafiltration membrane and its preparation method and application, as well as a component with the ultrafiltration membrane. The outgoing liquid surface pore density of the ultrafiltration membrane is relatively small, but by regulating the outgoing liquid surface of the ultrafiltration membrane to have a suitable pore size, the inner liquid surface and the outgoing liquid surface have an appropriate pore density and pore size ratio, and the membrane as a whole has a suitable porosity and pore size structure, a good overall flux of the membrane is achieved, and at the same time, the compressive strength of the outgoing liquid surface and the overall mechanical strength of the membrane are improved.

[0007] To achieve the above object, the present invention provides the following technical solution: a sulfone polymer hollow fiber ultrafiltration membrane, comprising a main body, one side of the main body is an inner liquid inlet surface facing the inner cavity, the other side of the main body is an outgoing liquid surface, the main body has a non-directional tortuous passage, the outgoing liquid surface includes a plurality of first holes, the SEM average pore size of the first holes is 50nm-1000nm, the pore density of the outgoing liquid surface is 20 / 25μm 2 -200 pieces / 25μm 2 ; The inner liquid inlet surface includes a plurality of second holes, and the ratio of the SEM average pore size of the second holes to the SEM average pore size of the first holes is 1:2-10; the ratio of the pore density of the inner liquid inlet surface to the pore density of the outgoing liquid surface is 0.8-15; the overall porosity of the ultrafiltration membrane is 30%-80%.

[0008] The ultrafiltration membrane of the present invention is prepared from sulfone polymers, which have the advantages of excellent mechanical properties, thermal stability, biocompatibility, easy phase separation and pore formation. When developing biological ultrafiltration membranes, technicians in this field hope to obtain a membrane structure in which the inner liquid inlet surface is small and has few holes, the outer liquid surface is large and the number of membrane holes is much larger than the number of membrane holes in the inner liquid inlet surface. Such a membrane structure is conducive to capturing the substances to be intercepted basically at the inner liquid inlet surface and its vicinity, and the filtration resistance is small and the flux is high, thereby achieving the ultrafiltration membrane retention efficiency and flux. Similarly, technicians in this field generally believe that once the number of holes in the outer liquid surface is less, that is, the number of holes in the inner liquid inlet surface is not much different (especially less than the number of holes in the inner liquid inlet surface), the overall flux of the ultrafiltration membrane will be greatly affected, resulting in too low overall flux of the membrane, thereby affecting the filtration efficiency. The inventors of the present invention have found through continuous research that even if the number of membrane holes in the outer liquid surface is not large, the membrane as a whole can have a good flux and high filtration efficiency under a specific ultrafiltration membrane structure. First, the above-mentioned specific membrane structure refers to holes with suitable pore sizes on both the inner liquid inlet surface and the outer liquid surface, and the SEM average pore size of the first hole on the outer liquid surface is controlled to be 50-1000nm and the ratio of the SEM average pore size of the second hole on the inner liquid inlet surface to the pore size of the first hole on the outer liquid surface is 1:2-10, that is, the first hole and the second hole both have suitable pore sizes, and at the same time, the pore size of the first hole is larger than the pore size of the second hole, and the pore size of the second hole has a suitable ratio to the pore size of the first hole, which can ensure that the substances to be intercepted are captured on the inner liquid inlet surface, and the corresponding amount; secondly, the above-mentioned specific membrane structure refers to the overall porosity of the ultrafiltration membrane of 30%-80%. The overall porosity mainly reflects the overall structural characteristics of the membrane, that is, the number of pores in the ultrafiltration membrane of the present invention is relatively large. At the same time, the ultrafiltration membrane of the present invention refers to a 1kD-750kD membrane. Preferably, the ultrafiltration membrane of the present invention is a 1kD-100kD membrane. More preferably, the ultrafiltration membrane of the present invention is a 5kD-100kD membrane, that is, the pore size of the membrane is relatively small, that is, the ultrafiltration membrane of the present invention has a suitable number of pores and a suitable pore size as a whole, which is conducive to ensuring the flux requirements. Based on the above-mentioned membrane structure containing the specific pore size of the first pore, the ratio of the pore size of the second pore to the pore size of the first pore, and the number of pores and pore size characteristics of the entire membrane, by controlling the pore density of the outgoing liquid surface to 20 / 25μm 2 -200 pieces / 25μm 2The ratio of the pore density of the inner liquid inlet surface to the pore density of the outgoing liquid surface is 0.8-15, that is, when the number of holes on the outgoing liquid surface is slightly more or even less than the number of holes on the inner liquid inlet surface, the membrane as a whole still has a good flux. Of course, the number of holes on the outgoing liquid surface cannot be too small, because when the number of holes on the outgoing liquid surface is too small, its flux will not meet the filtration requirements, thereby affecting the filtration efficiency. Therefore, in the present invention, the pore density of the outgoing liquid surface is 20 / 25μm. 2 -200 pieces / 25μm 2 The ratio of the pore density of the inner liquid inlet surface to the pore density of the outer liquid surface is 0.8-15. With the support of the above-mentioned specific membrane structure, a good overall membrane flux is still obtained, which overcomes the technical bias existing in the prior art and is therefore creative.

[0009] Since the pore density of the outgoing liquid surface in the present invention is relatively small, that is, the number of the first holes on the outgoing liquid surface is relatively small, and the pore size of the first holes cooperates with each other, the outgoing liquid surface has a higher compressive strength, thereby improving the mechanical strength of the membrane as a whole, and reducing the membrane contamination of the outgoing liquid surface, because if the pore density on the outgoing liquid surface is greater than 200 / 25μm 2 That is, when the number of holes on the outgoing liquid surface is relatively large, the pressure resistance of the outgoing liquid surface will decrease. Under normal operating pressure, the outgoing liquid surface of the ultrafiltration membrane will cause membrane filament collapse due to insufficient pressure resistance, and cannot meet practical needs. At the same time, if the membrane is in a non-clean environment before being prepared into a hollow fiber membrane assembly, various small particles in the air can easily enter the membrane filament through the membrane pores on the outgoing liquid surface, thereby increasing the probability of contaminating the membrane filament, causing blockage of the membrane pores and reducing the membrane flux on the one hand, and affecting the cleanliness of subsequent products on the other.

[0010] In addition, since the membrane filaments are usually bonded by colloids when they are prepared into membrane components, and the hollow fiber ultrafiltration membrane prepared by the present invention uses sulfone polymers as raw materials, in order to ensure the protein yield, its hydrophilicity is relatively high, and its surface energy is generally not less than 60mN / m, while the surface energy of commonly used polymers PP and PE is about 30mN / m, and the surface energy of colloids is usually below 50mN / m. Because colloids have better bonding strength when bonding to polymers with higher surface energy than when bonding to polymers with lower surface energy, when sulfone polymers are used as raw materials to prepare hollow fiber membranes and then processed into hollow fiber components, the membrane filaments have relatively good bonding strength. At the same time, the inventors of the present application unexpectedly found that the pore density at the outgoing liquid surface is 20 / 25μm. 2 -200 pieces / 25μm 2The synergistic effect of the first pores on the outgoing liquid surface having an average pore size of 50-1000 nm under the SEM can maintain a strong bonding force between the membrane fibers, and at the same time prevent the colloid from excessively blocking the membrane pores or even the inner cavity of the membrane fibers, thereby causing waste of the membrane fibers. The inventors of the present application found during the research that when the pore density of the outgoing liquid surface is less than 20 / 25 μm 2 Or when the SEM average pore size of the first hole on the outgoing liquid surface is less than 50nm, the bonding force between the membrane fibers is insufficient, resulting in the problem of separation between the membrane fibers, which in turn affects the strength of the membrane fibers in the hollow fiber assembly and affects the filtration efficiency; at the same time, when the pore density on the outgoing liquid surface is higher than 200 / 25μm 2 Or when the SEM average pore size of the first hole out of the liquid surface is greater than 1000nm, the amount of colloid entering the hole will be too much. Although it can increase the bonding strength between the membrane filaments, it will block the membrane pores too much and even further block the inside of the membrane filaments, making it impossible to meet the liquid inlet of the ultrafiltration process. It is usually necessary to cut the blocked inner cavity area and re-seal the membrane filaments, resulting in waste of membrane filaments.

[0011] In summary, the inventors of the present application have achieved the goal of ensuring the flux of the ultrafiltration membrane even when the pore density of the outgoing liquid surface is small (fewer pores) by regulating the SEM average pore size of the outgoing liquid surface of the membrane, the ratio of the SEM average pore size of the inlet liquid surface to the SEM average pore size of the outgoing liquid surface, and the overall porosity and pore size of the ultrafiltration membrane, thereby overcoming the technical prejudice that the membrane flux is too low when the number of holes on the outgoing liquid surface is relatively small; at the same time, the small pore density of the outgoing liquid surface brings about excellent compressive strength of the outgoing liquid surface, improves the overall mechanical strength of the membrane, and reduces the risk of contamination of the outgoing liquid surface; in addition, under the synergistic effect of the above-mentioned specific outgoing liquid surface pore density and the SEM average pore size of the first hole, the membrane filaments of the prepared hollow fiber assembly have strong bonding force, thereby improving the strength of the membrane filaments in the prepared hollow fiber assembly, improving the filtration efficiency, and being able to meet the needs of practical applications.

[0012] During the membrane preparation process, in the direction perpendicular to the membrane thickness (if the membrane is a flat membrane, the direction is the plane direction, if the membrane is a hollow fiber membrane, the direction is perpendicular to the radius direction), its various characteristics such as the pore size are roughly uniform and basically consistent, so the pore size of the pores in the corresponding plane can be used to reflect the overall pore size on the plane. The pore density on the outgoing liquid surface of the ultrafiltration membrane and the pore density on the inlet liquid surface can be characterized by scanning electron microscopy of the membrane structure, and then measured by computer software (such as Matlab, NIS-Elements, etc.) or manually, and the corresponding calculations can be performed. When actually measuring the pore density on the outgoing liquid surface and the ingoing liquid surface of the ultrafiltration membrane, the outgoing liquid surface and the ingoing liquid surface of the membrane can be characterized by a microscope (the outgoing liquid surface of the hollow fiber membrane is magnified to a degree that can clearly confirm the shapes of as many holes as possible, such as 5000 times, 10000 times, 20000 times, etc.), and the corresponding SEM images are obtained. Since the pore sizes on the outgoing liquid surface and the ingoing liquid surface of the membrane are roughly uniform, a certain area, such as 400 μm, is selected. 2 (20 μm x 20 μm), 225 μm 2 (15 μm x 15 μm), 100 μm 2 (10 μm x 10 μm), 25 μm 2 (5μm x 5μm), 1μm 2 (1 μm multiplied by 1 μm), the specific area size depends on the actual situation, and then count the number of holes on the selected area, calculate the pore density on the selected area, perform several tests (preferably more than 10 times, the specific number depends on the situation), take the average value, and you will get the pore density value of the outgoing liquid surface and the internal liquid inlet surface. The SEM average pore size of the first hole on the outgoing liquid surface is also measured by a scanning electron microscope. The outgoing liquid surface of the hollow fiber membrane is photographed at a magnification of 5000 times, 10000 times, 20000 times, etc., which can clearly confirm the shape of as many holes as possible. The corresponding SEM image is obtained. The hole formed on the outgoing liquid surface is circular, elliptical or nearly elliptical. The longest line segment in the line segment connecting the two points on the periphery of the hole is measured by corresponding computer software or manually as the major diameter, and then the longest line segment in the line segment connecting the two points on the periphery of the hole perpendicular to the major diameter is measured as the SEM average pore size of the first hole. Several tests are performed (preferably more than 10 times, the specific number depends on the situation), and the average value is calculated as the SEM average pore size of the first hole described in the present invention. The SEM average pore size of the second hole on the inner liquid surface is also measured by the same test method as the SEM average pore size of the first hole on the outgoing liquid surface. Of course, those skilled in the art can also obtain the above parameters by other measurement methods, and the above measurement methods are for reference only.

[0013] The non-directional tortuous pathways of the present invention refer to randomly oriented groove structures and / or discretely distributed hole structures, and each non-directional tortuous pathway is interconnected.

[0014] The several holes refer to 2 or more holes.

[0015] The pore density refers to the number of pores within a certain area, for example, 1 μm 2 (1μm×1μm), 4μm 2 (2μm×2μm), 9μm 2 (3μm×3μm), 16μm 2 (4μm×4μm), 25μm 2 (5μm×5μm)...the number of holes in the area.

[0016] Commonly used testing methods for porosity include mercury injection method, density method and dry and wet film weighing method, etc. Of course, those skilled in the art can also obtain the above parameters through other testing methods. The above testing methods are for reference only.

[0017] As a further improvement of the present invention, the average pore size of the second pores by SEM is 3nm-450nm; the pore density of the inner liquid inlet surface is 30 / 25μm 2 -800 pieces / 25μm 2 ; and / or, the ratio of the pore density of the inner liquid inlet surface to the pore density of the outer liquid surface is 1.1-10.

[0018] In biological ultrafiltration, most of the substances to be intercepted are basically captured at the inner liquid inlet surface and its vicinity. Therefore, the SEM average pore size value of the second hole will have a great influence on the overall retention efficiency of the membrane. In the present invention, the SEM average pore size of the second hole is controlled to be 3nm-450nm. Preferably, the SEM average pore size of the second hole is 5nm-300nm, and more preferably, the SEM average pore size of the second hole is 8nm-200nm. The second hole with such a pore size is suitable for fully capturing biological macromolecules. In practical applications, the pore size of the second hole can be adjusted according to different needs to ensure the retention efficiency. Since the ultrafiltration membrane of the present invention is an internal pressure filtration, it is necessary to adjust the number of holes on the inner liquid inlet surface. Through research, the pore density of the second holes on the inner liquid inlet surface is 30 / 25μm. 2 -800 pieces / 25μm 2, in coordination with the second holes on the inner liquid inlet surface having a suitable pore size, the inner liquid inlet surface has a suitable surface pore area ratio, which ensures that the inner liquid inlet surface has good pressure resistance, and can ensure the stability of the second holes during long-term internal pressure filtration, and is not easy to collapse or deform; at the same time, the impact of the relatively dense inner liquid inlet surface on the overall flux of the membrane is minimized as much as possible, and the overall flux of the membrane will not be too low; on the basis of the second holes with a preferred pore size and number on the inner liquid inlet surface, we further regulate the ratio of the pore density of the inner liquid inlet surface to the pore density of the outgoing liquid surface to 1.1-10, that is, we hope that the number of first holes on the outgoing liquid surface is less than the number of second holes on the inner liquid inlet surface, further ensuring the pressure resistance of the outgoing liquid surface of the membrane and then making the membrane as a whole have a higher pressure resistance, while further reducing the possibility of ultrafiltration membrane contamination, and reducing various problems caused by glue blocking the membrane pores during the assembly of membrane filaments into components.

[0019] As a further improvement of the present invention, the surface energy of the liquid surface of the ultrafiltration membrane is not less than 60mN / m, preferably 65mN / m-90mN / m; the roughness of the liquid surface of the ultrafiltration membrane is 3μm-50μm, preferably 5μm-35μm;

[0020] The average pore size of the first pores under SEM is 80nm-400nm, and the pore density of the outgoing liquid surface is 25 / 25μm. 2 -150 pieces / 25μm 2 .

[0021] As is well known, the hydrophilicity and hydrophobicity of the ultrafiltration membrane will have a great influence on the yield of protein substances. In general, the better the hydrophilicity of the membrane, the higher the yield of the product protein substances; therefore, in the present invention, the ultrafiltration membrane also needs to be relatively hydrophilic. After research, it is found that the surface energy of the outgoing liquid surface of the ultrafiltration membrane is regulated to be not less than 60mN / m, preferably 65mN / m-90mN / m, which has good hydrophilicity, thereby ensuring the product yield; but in the present invention, we do not want the outgoing liquid surface to be too hydrophilic (especially when the protein substances such as concentration and purification are basically captured by the incoming liquid surface), because once the outgoing liquid surface is too hydrophilic, on the one hand, it may aggravate membrane pollution, and the enhanced hydrophilicity easily leads to the enhanced interaction force between the outgoing liquid surface of the membrane and the pollutants, thereby increasing the adsorption of pollutants on the membrane surface, and on the other hand, it will make it easier for colloids to penetrate the interior of the ultrafiltration membrane, increase the colloid blocking the membrane pore structure inside the ultrafiltration membrane, resulting in too low membrane flux and too low pollution holding capacity.

[0022] On the basis that the outgoing liquid surface of the membrane has appropriate surface energy, the roughness of the outgoing liquid surface is further adjusted to 3μm-50μm. The roughness of the outgoing liquid surface is low and the surface is relatively smooth, which is beneficial to reducing the area of ​​attachment of pollutant particles, while weakening the interaction between pollutants and the membrane surface, effectively reducing the accumulation of pollutants on the membrane surface, and improving the anti-fouling performance of the membrane; at the same time, a certain amount of colloid can penetrate into the membrane to ensure adhesion, which will neither cause clogging of the membrane pores nor increase the difficulty of processing, and the membrane filaments can be firmly bonded through the colloid.

[0023] On the basis of the appropriate surface energy and roughness of the outgoing liquid surface, the membrane pore structure on the outgoing liquid surface is further regulated, and the SEM average pore size of the first pore is further preferably 80-400nm, and the pore density of the outgoing liquid surface is 25 / 25μm 2 -150 pieces / 25μm 2 The synergistic effect of these features not only makes the outgoing liquid surface have excellent compressive strength, but also has better membrane filament bonding strength and lower membrane pollution.

[0024] The surface energy result is measured by a dyne pen; the roughness result is measured by an ultra-depth of field three-dimensional microscope; of course, those skilled in the art can also obtain the above parameters by other testing methods, and the above testing methods are for reference only.

[0025] As a further improvement of the present invention, in the thickness direction from the inner liquid inlet surface to the outer liquid surface of the ultrafiltration membrane, the average pore size of the main body first increases and then decreases; the main body includes a large pore area, and the closest average distance A from the large pore area to the outer liquid surface is not less than 15 μm; and the closest average distance B from the large pore area to the inner liquid inlet surface is not less than 15 μm, and the overall porosity of the ultrafiltration membrane is 35%-70%.

[0026] In the main structure of the sulfone polymer hollow fiber ultrafiltration membrane provided by the present invention, it can also be clearly seen that in the thickness direction from the inner liquid inlet surface to the outer liquid surface of part of the ultrafiltration membrane, the average pore size of the main body first increases and then decreases. The membrane pore structure changes in this way, so that a large pore area appears in the main structure of the membrane. The large pore area can be considered as the area with the largest pore size inside the membrane. The ratio of the SEM average pore size of the large pore area to the SEM average pore size of the first pore is not less than 1.5. The existence of the large pore area can further increase the flux of the entire membrane, so that the ultrafiltration membrane prepared by the present invention has a better overall flux; at the same time, since the large pore area is the area with larger membrane pores inside the membrane, if the large pore area is too close to the inner liquid inlet surface or the outer liquid surface, it is easy to cause the first pore and the second pore The collapse and deformation of the macropore area have a great impact on the stability of the interception efficiency and the flux. At the same time, when the macropore area is too close to the outgoing liquid surface, it is easy to increase the risk of excessive colloid entering the membrane filaments. Therefore, after research, the average distance A from the macropore area to the outgoing liquid surface and the average distance B from the inner inlet liquid surface in the present invention are not less than 15 μm, that is, the macropore area is not very close to the inner outlet liquid surface and the outgoing liquid surface, and under the synergistic effect of the overall membrane porosity of 35%-70%, the obtained ultrafiltration membrane has a better overall flux, and the compressive strength of the inner inlet liquid surface and the outgoing liquid surface of the membrane is basically unchanged, the overall mechanical strength of the membrane is still high, and it can also prevent the colloid from excessively penetrating into the inner cavity of the membrane filaments, blocking the inner cavity of the membrane filaments, and affecting the difficulty of making the membrane filaments into membrane components.

[0027] The location of the macroporous region is determined in the present invention by using a scanning electron microscope to characterize the morphology of the entire membrane cross section, for example, obtaining a scanning electron microscope image of the entire membrane at a magnification of 400, 500 or 700, determining the region L with the largest membrane pores, and then continuously photographing the region L, for example, obtaining multiple membrane cross-sectional electron microscope images at a magnification of 10,000, 15,000 or 20,000, and measuring the pore sizes of the multiple membrane cross-sectional electron microscope images obtained at magnifications of the L region, by selecting multiple holes on the same plane to measure their pore sizes, and calculating the average value, and the maximum value obtained is the maximum pore size of the macroporous region of the membrane. Aperture; then, the membrane cross section between the plane of the maximum pore size and the outgoing liquid surface is continuously photographed to obtain multiple membrane cross-section electron microscope images with a magnification of 10,000, 15,000 or 20,000, and then the average value of the membrane pores in the corresponding plane area is gradually measured from the plane of the maximum pore size toward the outgoing liquid surface, until the average value of the membrane pores is 0.75 times the average value of the maximum pore size, and the plane with the average value of the membrane pores is determined as the interface P1 of the membrane macropore area close to the outgoing liquid surface, and the same method is used to determine the interface P2 of the membrane macropore area close to the inner liquid surface, and the area between the interface P1 and the interface P2 is called the macropore area. The average value of the distance between the above interface P1 and the outgoing liquid surface is called the closest average distance A from the macropore area to the outgoing liquid surface, and the average value of the distance between the interface P2 and the inner liquid surface is the closest average distance B from the macropore area to the inner liquid surface. The SEM average pore size of the macroporous area is characterized by scanning electron microscopy at a certain magnification, such as 2000 times, 5000 times or 10000 times, uniformly selecting points at different positions (preferably more than 10 points) as measurement objects, using corresponding computer software (such as Matlab, NIS-Elements, etc.) or manually measuring the corresponding SEM pore size, and then calculating the average value to obtain the SEM average pore size of the macroporous area. The measurement method of the nearest average distance A and the nearest average distance B is to measure the distance from multiple interfaces P1 / P2 to the outgoing liquid surface / ingoing liquid surface on the cross-sectional SEM image of the membrane by computer software (such as Matlab, NIS-Elements, etc.) or manually, and calculate the average value.

[0028] As a further improvement of the present invention, the thickness of the macroporous region is 40-120 μm; the ratio of the thickness of the macroporous region to the overall thickness of the membrane is 0.25-0.6; and / or the ratio of the SEM average pore size of the macroporous region to the SEM average pore size of the first hole is 3-20.

[0029] The macroporous region is a region with larger membrane pores inside the membrane, and is also one of the important factors affecting the overall flux of the membrane. The ratio of the SEM average pore size of the macroporous region of the membrane prepared by the present invention to the SEM average pore size of the first hole is 3-20, that is, the SEM average pore size of the macroporous region is slightly larger than the SEM average pore size of the first hole (for example, it can be 3 times, 5 times, 8 times, 10 times, 12 times, etc.), which can improve the overall flux of the membrane. At the same time, when the fluid enters or flows out of the macroporous region, the flow rate of the fluid is relatively stable, which can avoid the cross-sectional fibers forming the membrane pore structure from being damaged due to the huge change in flow rate. The inventor of the present application unexpectedly found that when the ratio of the SEM average pore size of the macroporous region to the SEM average pore size of the first hole is slightly larger, the thickness of the macroporous region can be thicker (for example, the ratio of the thickness of the macroporous region to the thickness of the entire membrane is greater than 0.25), which further improves the overall flux of the membrane by increasing the thickness of the macroporous region. We were pleasantly surprised to find that the SEM average pore size of the large pore area was slightly larger than that of the first hole, and under the synergistic effect of the thicker large pore area, the first hole and the second hole did not collapse or deform, and both the inner liquid surface and the outer liquid surface had good compressive strength, and could still maintain stable retention efficiency and flux. If the ratio of the SEM average pore size of the macropore zone to the SEM average pore size of the first hole exceeds 20, although the overall flux of the membrane can be improved, it will bring the risk of unstable membrane structure; if the thickness of the macropore zone is greater than 120 μm or the thickness of the macropore zone accounts for more than 60% of the overall thickness of the membrane, that is, the thickness of the macropore zone is too large or the thickness of the macropore zone accounts for too much of the overall thickness of the membrane, the first hole and the second hole of the ultrafiltration membrane prepared therefrom will collapse and deform, but the retention efficiency and flux stability of the membrane will be affected; if the ratio of the SEM average pore size of the macropore zone to the SEM average pore size of the first hole is too small, it cannot further improve the overall flux of the membrane. If the thickness of the macropore zone is too thin or the ratio of the thickness of the macropore zone to the overall thickness of the membrane is too low, the overall flux of the ultrafiltration membrane is also limited (because the presence of the macropore zone can increase the flow area of ​​the fluid, thereby increasing the fluid flux of the macropore zone, and then increasing the overall flux of the membrane, especially for internal pressure ultrafiltration membranes, the fluid flows from the inner inlet surface to the outer liquid surface, and the presence of the macropore zone can reduce the flow resistance). Therefore, through the synergistic effect of the ratio of the SEM average pore size of the large pore area being 3-20, when the membrane thickness of the large pore area is thicker or the thickness of the large pore area accounts for a larger proportion of the overall thickness of the membrane, the obtained ultrafiltration membrane not only has excellent and stable overall membrane flux, but also can still maintain the compressive strength of the membrane's outflowing liquid surface and the inflowing liquid surface, and the overall mechanical strength of the membrane.

[0030] The thickness and other parameters of the macropore area in the present invention can be characterized by using a scanning electron microscope to characterize the morphology of the membrane cross-sectional structure, and then using computer software (such as Matlab, NIS-Elements, etc.) or manually to measure the distance between the interface P1 and the interface P2 for multiple times, and calculate the average value. Of course, those skilled in the art can also obtain the above parameters by other testing methods. The above testing methods are for reference only (the thickness and other parameters of the micropore area below can also be obtained by this method).

[0031] As a further improvement of the present invention, the closest average distance A from the macropore area to the outgoing liquid surface is 20μm-60μm, and the ratio of the distance A to the membrane thickness is 0.1-0.5; and / or, the ratio of the closest average distance A from the macropore area to the outgoing liquid surface to the closest average distance B from the macropore area to the inner liquid surface is 0.6-2.5.

[0032] Because the macroporous region is the area with larger membrane pores inside the membrane, the distance from the macroporous region to the outgoing liquid surface cannot be too close, otherwise it is easy to cause damage to the first hole, thereby affecting the stability of the membrane interception efficiency and flux, as well as affecting the compressive strength of the outgoing liquid surface and the mechanical strength of the membrane as a whole. At the same time, the colloid will enter the membrane filaments too much, blocking the membrane pores and affecting the cleanliness of subsequent products. Therefore, preferably, the nearest average distance A from the macroporous region to the outgoing liquid surface is 20-60 μm, that is, the macroporous region will not be too close to the outgoing liquid surface, and the obtained ultrafiltration membrane has excellent overall flux, stable compressive strength of the membrane outlet liquid surface, excellent mechanical strength of the membrane as a whole, and controls the colloid to enter the membrane filaments in an appropriate amount to reduce the difficulty of membrane assembly preparation, while not causing excessive clogging of membrane pores and membrane pollution.

[0033] Furthermore, if the ratio of the closest average distance A from the large pore area to the outgoing liquid surface to the membrane thickness is too large, that is, the distance between the large pore area and the outgoing liquid surface is too far, although it can ensure that the first hole will not collapse and deform, the colloid cannot reach the bonding force required when the membrane filament is prepared into an assembly due to the difficulty of entering the membrane filament, thereby increasing the difficulty of preparing the membrane assembly; at the same time, when the ratio of the closest average distance A from the large pore area to the outgoing liquid surface to the membrane thickness is too low, that is, when the large pore area is too close to the outgoing liquid surface, it will cause the collapse and deformation of the first hole, and the retention efficiency and flux stability will be greatly affected. At the same time, it is also easy to cause excessive colloid to enter the membrane filament to block the membrane pores and increase product contamination. Therefore, by adjusting the ratio of distance A to membrane thickness to 0.1-0.5, the ultrafiltration membrane obtained has better overall membrane flux, compressive strength of the membrane outgoing liquid surface, and overall mechanical strength of the membrane, and is easy to make into a membrane assembly.

[0034] Furthermore, by regulating the ratio of the closest average distance A from the large pore area to the outgoing liquid surface and the closest average distance B from the large pore area to the inner liquid surface to be 0.6-2.5, that is, the large pore area is neither particularly close to the outgoing liquid surface nor particularly close to the inner liquid surface, that is, the large pore area is in a relatively middle position of the membrane, which can play a certain buffering role, that is, the distance from the inner liquid surface to the large pore area interface P2 is similar to the distance from the large pore area interface P1 to the outgoing liquid surface, which can optimize the pressure distribution, reduce the deformation or damage of the membrane filaments due to uneven pressure, and thereby improve the overall mechanical strength of the membrane. Therefore, the closest average distance A from the large pore area to the outgoing liquid surface is 20μm-60μm, and the ratio of the distance A to the membrane thickness is 0.1-0.5. At the same time, under the synergistic effect of the ratio of the closest average distance A from the large pore area to the outgoing liquid surface and the closest average distance B from the large pore area to the inner liquid surface being 0.6-2.5, the obtained ultrafiltration membrane has better overall membrane flux, compressive strength of the membrane outgoing liquid surface, mechanical strength of the entire membrane, the prepared membrane filaments are easy to prepare into membrane components and have excellent bonding strength between the membrane filaments, and the distribution of the fluid is optimized.

[0035] As a further improvement of the present invention, the macroporous region has a first cross-sectional fiber forming a porous structure, and the SEM average diameter of the first cross-sectional fiber is 20nm-180nm; and / or the ratio of the SEM average pore size of the macroporous region to the SEM average diameter of the first cross-sectional fiber is 5-30.

[0036] The above-mentioned large pore area has a first cross-section fiber that forms a porous structure. If the SEM average diameter of the first cross-section fiber is too small, it cannot play a role in supporting the holes in the large pore area. At the same time, the first cross-section fiber with a too small SEM average diameter is easy to break during the ultrafiltration process, and then two or more holes are connected to form holes with larger pore sizes, or even connected into finger-shaped holes, which will cause a large flow rate change when the fluid passes through the large pore area, and then it is easier to damage other first cross-section fibers, resulting in a decrease in the overall mechanical strength of the membrane. The change in the flow rate of the fluid in the large pore area will also cause the collapse of the holes on the outgoing liquid surface, thereby affecting the compressive strength of the outgoing liquid surface; and if the SEM average diameter of the first cross-section fiber is too large, the overall porosity of the membrane will be reduced, affecting the filtration efficiency. Therefore, by adjusting the SEM average diameter of the first cross-section fiber to 20-180nm, the first cross-section fiber can meet the support for the holes in the large pore area, further improving the compressive strength of the outgoing liquid surface and the overall mechanical strength of the membrane. Furthermore, by studying and regulating the ratio of the SEM average pore size of the large pore zone to the SEM average pore size of the first cross-section fiber to be 5-30, under the synergistic effect of the appropriate SEM average diameter of the first cross-section fiber in the large pore zone, the large pore zone has a suitable porosity and the membrane as a whole has a better flux. At the same time, even if ultrafiltration is carried out under a certain operating pressure, the obtained ultrafiltration membrane still has excellent overall mechanical strength of the membrane.

[0037] The SEM average diameter of the first cross-section fiber can be measured by using a scanning electron microscope to characterize the morphology of the membrane cross-section in the large pore area, and then using computer software (such as Matlab, NIS-Elements, etc.) or manually measuring and performing corresponding calculations. For example, first use an electron microscope to characterize the membrane cross-section in the large pore area to obtain the corresponding SEM image. The specific area size depends on the actual situation. Then use the corresponding computer software or manually measure the diameter of the first cross-section fiber on the area (preferably more than 10 times, the specific number depends on the situation), and then calculate to obtain the average diameter of the fiber on the first cross-section. Of course, those skilled in the art can also obtain the above parameters by other measurement methods. The above measurement methods are for reference only. (The SEM average diameter of the second cross-section fiber hereinafter can also be tested in a similar way)

[0038] As a further improvement of the present invention, in the thickness direction from the inner liquid inlet surface to the outer liquid surface of the ultrafiltration membrane, the average pore size of the main body first increases, then decreases, and then increases again, the main body includes a small pore area, the small pore area is located between the large pore area and the outer liquid surface, and the shortest average distance C from the small pore area to the outer liquid surface is not less than 2μm; the overall porosity of the ultrafiltration membrane is 40%-65%.

[0039] In the main structure of the sulfone polymer hollow fiber ultrafiltration membrane provided by the present invention, it can be further clearly seen that in the thickness direction from the inner liquid inlet surface to the outer liquid surface of the part of the ultrafiltration membrane, the average pore size of the main body first increases, then decreases, and then increases again. The membrane pore structure changes in this way, so that a small pore area appears between the large pore area and the outer liquid surface. The small pore area can be considered as an area with relatively small pores inside the membrane. The SEM average pore size of the small pore area is less than 0.5 of the SEM average pore size of the large pore area. The existence of the small pore area can play a supporting role for the large pore area, so that the large pore area of ​​the ultrafiltration membrane prepared by the present invention is not easy to collapse or deform, thereby ensuring a more stable flux and retention efficiency of the ultrafiltration membrane as a whole while ensuring the overall mechanical strength of the ultrafiltration membrane.

[0040] Since the small pore area is an area with smaller membrane pores inside the membrane, if the small pore area is too close to the outgoing liquid surface, pollutants on the outgoing liquid surface can easily enter the small pore area in a non-clean environment, causing blockage of the small pore area, which in turn affects the membrane assembly. The colloid penetrates into the membrane filaments, causing insufficient adhesion between the membrane filaments and affecting the quality of the hollow fiber assembly. Therefore, after research, the nearest average distance C from the small pore area to the outgoing liquid surface in the present invention is not less than 2μm, that is, the small pore area is not too close to the outgoing liquid surface, and under the synergistic effect of the overall membrane porosity of 40%-65%, the obtained ultrafiltration membrane has better overall membrane mechanical strength, and the membrane filaments have suitable adhesion when prepared into membrane assemblies, while still maintaining a better overall membrane flux.

[0041] The position of the small hole area is determined in the present invention. After the cross section on the side close to the outgoing liquid surface is characterized by the morphology using a scanning electron microscope, for example, a scanning electron microscope image of a partial cross section of the membrane with a magnification of 1000, 2000 or 3000 is obtained, and the area S with the smallest membrane pores between the large hole area and the outgoing liquid surface is obtained. Then, the area S is continuously photographed, for example, multiple membrane cross-section electron microscope images with a magnification of 10000, 15000 or 20000 are obtained, and the pore diameters of the multiple membrane cross-section electron microscope images obtained in the S area at magnifications are measured. The method is to select multiple holes on the same plane to measure their pore diameters, and calculate the average value. The minimum value obtained is is the minimum pore size of the membrane pore area; then the membrane cross section between the plane of the minimum pore size and the outgoing liquid surface is continuously photographed to obtain multiple membrane cross-section electron microscope images with a magnification of 10,000, 15,000 or 20,000, and then the average value of the membrane pores in the corresponding plane area is gradually measured from the plane of the minimum pore size to the outgoing liquid surface, until the average value of the membrane pores is 1.2 times the average value of the minimum pore size of the membrane pore area, the plane with the average value of the membrane pores is determined as the interface P3 of the membrane pore area close to the outgoing liquid surface, and the same method is used to determine the interface P4 of the membrane pore area close to the large pore area, and the area between the interface P3 and the interface P4 is called the pore area. The average value of the distance between the above interface P3 and the outgoing liquid surface is called the closest average distance C from the pore area to the outgoing liquid surface. The SEM average pore size of the small hole area is characterized by scanning electron microscopy at a certain magnification, such as 2000 times, 5000 times or 10000 times, uniformly selecting points at different positions (preferably more than 10 points) as measurement objects, using corresponding computer software (such as Matlab, NIS-Elements, etc.) or manually measuring the corresponding SEM pore size, and then calculating the average value to obtain the SEM average pore size of the small hole area. The method for measuring the nearest average distance C is to measure the distance from the interface P3 of multiple small hole areas to the outgoing liquid surface on the cross-sectional SEM image of the membrane by computer software (such as Matlab, NIS-Elements, etc.) or manually, and calculate the average value.

[0042] As a further improvement of the present invention, the thickness of the small pore area is 5 μm-30 μm; the ratio of the thickness of the small pore area to the overall thickness of the membrane is 0.05-0.15; and / or the ratio of the thickness of the small pore area to the thickness of the large pore area is 0.1-0.4.

[0043] As everyone believes, the small pore zone is the area with smaller membrane pores inside the membrane. The existence of the small pore zone will lead to a decrease in the overall flux of the membrane. If the thickness of the small pore zone is too large, the overall flux of the membrane will drop sharply; if the thickness of the small pore zone is too small, it cannot guarantee the support for the large pore zone. Therefore, by adjusting the thickness of the small pore zone to 5μm-30μm, the ultrafiltration membrane obtained within this thickness range can not only guarantee the support for the large pore zone, so that the holes in the large pore zone will not collapse and deform, thereby ensuring the better mechanical strength of the membrane as a whole, the overall stable flux and retention efficiency of the membrane, and at the same time ensure that the overall flux of the membrane will not drop sharply due to the existence of the small pore zone.

[0044] Furthermore, by controlling the ratio of the thickness of the small pore area to the overall thickness of the membrane within the range of 0.05-0.15, the overall mechanical strength of the ultrafiltration membrane can be improved, and the overall stable flux and retention efficiency stability of the membrane will not be affected. It can also be further ensured that the obtained ultrafiltration membrane has a suitable overall membrane flux.

[0045] At the same time, by further controlling the ratio of the thickness of the small pore area to the thickness of the large pore area in the range of 0.1-0.4, it can be ensured that the small pore area of ​​the obtained ultrafiltration membrane plays a supporting role for the large pore area, and the overall flux of the ultrafiltration membrane will not be substantially affected. Therefore, under the synergistic effect of the small pore area thickness being within a reasonable range, the ratio of the small pore area thickness to the overall membrane thickness being within a reasonable range, and the thickness of the small pore area to the thickness of the large pore area being within a reasonable range, the prepared ultrafiltration membrane has a stable membrane structure and excellent mechanical strength, thereby ensuring better stable flux and retention efficiency, and the obtained ultrafiltration membrane still has a suitable overall membrane flux.

[0046] As a further improvement of the present invention, the SEM average pore size of the small pore zone is 0.1-0.4 of the SEM average pore size of the large pore zone, and / or the small pore zone has a second cross-sectional fiber forming a porous structure, and the SEM average diameter of the second cross-sectional fiber is 10nm-150nm.

[0047] The present invention adjusts the SEM average pore size of the small pore area to 0.1-0.4 of the SEM average pore size of the large pore area, that is, the SEM average pore size of the small pore area is smaller than that of the large pore area. Compared with the SEM average pore size of the large pore area, the small pore area can better support the large pore area when the SEM average pore size is smaller; at the same time, under the SEM average pore size ratio, the colloid can enter the membrane filaments in an appropriate amount, that is, the bonding force between the membrane filaments when preparing a hollow fiber membrane component can be guaranteed, and the membrane pores will not be excessively blocked to cause pollution inside the membrane; when the ratio of the SEM average pore size of the small pore area to the SEM average pore size of the large pore area is within a reasonable range, the flow rate of the fluid in the large pore area when flowing to the small pore area is relatively stable, and the cross-sectional fiber of the small pore area will not be damaged, so that the prepared membrane has more excellent mechanical strength. Furthermore, under the synergistic effect of the SEM average diameter of the second cross-section fiber being 10nm-150nm, when the SEM average diameter of the second cross-section fiber is within a suitable proportion range, the mechanical strength of the small pore area can be well guaranteed, thereby better supporting the large pore area, thereby achieving the obtained ultrafiltration membrane having excellent mechanical strength, stable flux and retention efficiency, and at the same time being conducive to the preparation of high-quality hollow fiber membrane components.

[0048] As a further improvement of the present invention, the closest average distance C from the small hole area to the outgoing liquid surface is 4μm-20μm; the ratio of the distance C to the membrane thickness is 0.04-0.1; and / or the ratio of the closest average distance C from the small hole area to the outgoing liquid surface to the closest average distance A from the large hole area to the outgoing liquid surface is 1:2-15.

[0049] By regulating the minimum average distance C from the small hole area to the outgoing liquid surface to 4μm-20μm, that is, the small hole area is relatively close to the outgoing liquid surface, but not too close to the outgoing liquid surface, because if the small hole area is very close to the outgoing liquid surface, small particle pollutants in the air in a non-clean environment can easily enter the small hole area to block the membrane pores, affect the penetration of the colloid, and increase the difficulty of preparing the membrane component; if the small hole area is slightly far from the outgoing liquid surface, the effect of further improving the pressure resistance of the outgoing liquid surface is weakened. Therefore, setting the minimum average distance C from the small hole area to the outgoing liquid surface within a reasonable range can make the obtained ultrafiltration membrane have better outgoing liquid surface pressure resistance, further improve the overall mechanical strength of the membrane, and at the same time prepare high-quality hollow fiber membrane components.

[0050] Furthermore, by adjusting the ratio of the shortest average distance C from the small hole area to the outgoing liquid surface to the membrane thickness to 0.04-0.1, not only can the membrane filaments have excellent adhesion when the membrane is prepared into a membrane assembly, but the overall mechanical strength of the membrane can also be improved.

[0051] Furthermore, by controlling the ratio of the closest average distance C from the small pore area to the outgoing liquid surface to the closest average distance A from the large pore area to the outgoing liquid surface at 1:2-15, the overall mechanical strength of the membrane, the compressive strength of the outgoing liquid surface, and the convenience of preparation into a hollow fiber membrane component can be improved, while still having a good overall membrane flux.

[0052] In addition, under the overall synergistic effect of the small pore area and the large pore area, the overall flow rate of the membrane is relatively stable, which is beneficial to protecting the integrity of the fibers in the internal cross section of the membrane, and further protecting the holes inside the membrane from collapse or deformation, so that the prepared membrane has stable flux and retention efficiency. At the same time, under the overall synergistic effect of the small pore area and the large pore area, the overall mechanical strength of the membrane, the compressive strength of the internal liquid inlet surface and the external liquid surface, and the overall flux of the membrane can be further improved, and it is also easier to prepare into membrane components.

[0053] As a further improvement of the present invention, the initial water flux of the ultrafiltration membrane is 0.5LMH / psi-300LMH / psi, preferably 1LMH / psi-250LMH / psi; the water flux of the ultrafiltration membrane after 10 complete uses is more than 70% of the initial water flux; the tensile strength of the ultrafiltration membrane is 100cN-350cN, preferably 160cN-280cN, and the elongation at break is not less than 15%, preferably 20%-150%; the membrane thickness is 90μm-200μm.

[0054] Permeation flux is also called permeation rate, or flux for short, and refers to the amount of material that passes through a unit membrane area per unit time under a certain working pressure during the membrane separation process. The size of the flux reflects the speed of the filtration rate. The larger the flux, the faster the filtration rate of the membrane. The water flux of the sulfone polymer hollow fiber ultrafiltration membrane in the present invention is 0.5LMH / psi-300LMH / psi, and its flux can meet the needs of practical applications, indicating that the filtration speed of the ultrafiltration membrane is relatively fast. While ensuring the interception efficiency, the fluid can quickly pass through the ultrafiltration membrane, the time cost is relatively low, and the economic benefit is relatively high. At the same time, after the ultrafiltration membrane has been used completely for 10 times (one complete use means that the material to be filtered is separated and purified once through the hollow fiber membrane assembly, and then the hollow fiber membrane assembly is cleaned and regenerated with a cleaning liquid, and its water flux is tested as the water flux after one complete use. Accordingly, 10 times of separation, purification and cleaning means 10 complete uses), the water flux is more than 70% of the initial water flux. It can be seen that the ultrafiltration membrane prepared by the present invention has good anti-pollution performance and regeneration effect, and has a long service life.

[0055] After mechanical strength test, the tensile strength of the ultrafiltration membrane prepared by the present invention is 100cN-350cN, preferably 160cN-280cN, and the elongation at break is not less than 15%, preferably 20%-150%. It has excellent mechanical properties and high industrial practical value. This also shows that the compressive strength of the inner liquid inlet surface and the outer liquid surface of the ultrafiltration membrane are relatively high, and it can withstand the operating pressure and the change of the operating pressure in the ultrafiltration process for a long time, and can work normally for a long time under relatively high pressure.

[0056] Each sample was stretched at a uniform speed using a stretching machine at room temperature (stretching speed was 50 mm / min, and the distance between the upper and lower clamps was 30 mm) until it broke, thereby measuring the tensile strength and elongation at break. This was repeated three times and the average value was taken. The average value obtained was the final tensile strength value and elongation at break value.

[0057] As a further improvement of the present invention, the ultrafiltration membrane is sponge-shaped. Compared with the pore-shaped structure, the sponge-shaped hollow fiber ultrafiltration membrane has better compressive strength and overall mechanical strength and tensile strength of the membrane (the hollow fiber membrane with a pore-shaped structure has the disadvantages of easy breakage of internal fibers, which may cause the collapse of the entire membrane, poor pore size controllability, which may affect the filtration progress, and high requirements on the diameter of the fibers supporting the pore structure).

[0058] The second aspect of the present invention provides a method for preparing the sulfone polymer hollow fiber ultrafiltration membrane as described above, comprising the following steps:

[0059] Step 1: Prepare casting liquid and core liquid:

[0060] The casting solution comprises a sulfone polymer, a first organic solvent, a hydrophilic additive and a non-solvent; the solid content of the sulfone polymer in the casting solution is 15%-25%, and the viscosity of the casting solution is 10,000-100,000 cps;

[0061] The core liquid comprises a second organic solvent and water, wherein the mass content of the second organic solvent in the core liquid is 0-40%;

[0062] Step 2: Spinning: The casting liquid and the core liquid prepared in step 1 are extruded from the spinneret together to form a molded product having an inner liquid surface and an outer liquid surface, wherein the temperature of the casting liquid is 20-40° C.;

[0063] Step 3: Rapid preliminary phase separation: immersing the molded product obtained in step 2 into a first coagulation bath for rapid phase separation, the phase separation time is 0.1-1.2s, the temperature of the first coagulation bath is 5-50°C higher than the temperature of the casting solution, to form a green film; wherein the first coagulation bath contains water and a third organic solvent, and the mass content of the third organic solvent is greater than 50%;

[0064] Step 4: Complete phase separation: immersing the raw film obtained in step 3 into a second coagulation bath for complete phase separation, wherein the phase separation time is 30-80s, and the temperature of the second coagulation bath is not lower than the temperature of the casting solution; wherein the second coagulation bath contains water and a fourth organic solvent, and the mass content of the fourth organic solvent is not more than 30%;

[0065] Step 5: Cleaning and drying: The raw membrane obtained in step 4 is cleaned with pure water and then dried to obtain a sulfone polymer hollow fiber ultrafiltration membrane.

[0066] As a further improvement of the present invention, the sulfone polymer is at least one of bisphenol A polysulfone, polyethersulfone, polyphenylsulfone and sulfonated polyethersulfone; the first organic solvent, the second organic solvent, the third organic solvent and the fourth organic solvent are at least one of dimethylformamide, dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide; the hydrophilic additive is at least one of polyethylene glycol, polyvinyl pyrrolidone and polyvinyl alcohol; the non-solvent is at least one of water, isopropanol, glycerol and butanediol.

[0067] As a further improvement of the present invention, the temperature of the first coagulation bath is 5-15° C. higher than that of the casting solution, and / or the temperature of the second coagulation bath is 30-50° C. higher than that of the casting solution.

[0068] As a further improvement of the present invention, the mass content of the non-solvent in the casting solution is 1%-10%; and / or the mass content of the third organic solvent in the first coagulation bath is 55%-95%; and / or the mass content of the fourth organic solvent in the second coagulation bath is 0-25%.

[0069] As a further improvement of the present invention, the temperature of the first coagulation bath is 30-50°C higher than the temperature of the casting liquid; and / or, the temperature of the second coagulation bath is 10-45°C lower than the temperature of the first coagulation bath; and / or, when the phases are completely separated in step four, the raw film is stretched, and the stretching rate is 1%-5%.

[0070] When preparing the sulfone polymer hollow fiber ultrafiltration membrane of the present invention, a casting solution is first prepared, and the casting solution includes a membrane-forming substance sulfone polymer, a first organic solvent for dissolving the sulfone polymer, a hydrophilic additive and a non-solvent, wherein the hydrophilic additive is at least one of polyethylene glycol, polyvinyl pyrrolidone and polyvinyl alcohol. The addition of the hydrophilic additive and the non-solvent can effectively control the viscosity of the casting solution system and effectively improve the stability of the membrane flux. By adjusting the ratio of the sulfone polymer, the first organic solvent, the hydrophilic additive and the non-solvent, the casting solution has a suitable viscosity. The viscosity of the casting solution has a great influence on the structure and performance of the filter membrane finally formed, such as affecting the pore size, thickness, flow rate, etc. of the filter membrane, thereby ensuring that the finally obtained sulfone polymer hollow fiber ultrafiltration membrane has a suitable thickness, an ideal membrane pore structure and pore size, and is effectively used in biological ultrafiltration. The inner core used in the hollow fiber ultrafiltration membrane of the present invention during extrusion is a liquid composed of a second organic solvent and water. By reasonably controlling the mass content of the second organic solvent in the core liquid, it is possible to ensure that the pressure in the hollow fiber ultrafiltration membrane cavity is balanced with the external pressure, thereby stabilizing the cavity of the hollow fiber ultrafiltration membrane so that the overall wall thickness of the membrane is basically the same. In addition, under the joint action of other conditions such as a coagulation bath, by controlling the changes in the membrane phase separation process, a sulfone polymer hollow fiber ultrafiltration membrane with an ideal molecular weight cutoff and an ideal pore size distribution can be manufactured.

[0071] The second step is to extrude the prepared casting liquid and core liquid from the spinneret together. The casting liquid forms a molded product with an inner liquid inlet surface and an outer liquid surface in the nozzle, namely, a hollow fiber membrane. The extruded hollow fiber membrane has an inner liquid inlet surface facing the inner cavity and an outer liquid surface opposite to the cavity.

[0072] The rapid preliminary phase separation in step three is to immerse the molded product obtained in step two directly into the first coagulation bath for rapid phase separation, and the phase separation time is 0.1-1.2s. In such a short time, the phase separation of the membrane can only occur at the outgoing liquid surface of the membrane and near the outgoing liquid surface. Under the synergistic effect of the solid content of sulfone polymer being 15%-25%, the temperature of the first coagulation bath being 5-50°C higher than the casting liquid temperature, and the third organic solvent content of the first coagulation bath being greater than 50%, the phase separation speed in the first coagulation bath is relatively slow. Therefore, under the synergistic effect of the relatively slow phase separation speed and the extremely short phase separation time in the first coagulation bath, a structure with fewer pores on the outgoing liquid surface and relatively larger pore size is prepared. At the same time, since the inner liquid inlet surface is in direct contact with the core liquid, the mass content of the second organic solvent in the core liquid is lower than the mass content of the third organic solvent in the first coagulation bath and under the combined effect of the specific solid content and viscosity system of the casting liquid, the obtained ultrafiltration membrane has a suitable pore density of the inner liquid inlet surface and the SEM average pore size of the second holes, ensuring that the ratio of the SEM average pore size of the second holes of the inner liquid inlet surface of the ultrafiltration membrane to the SEM average pore size of the first holes of the outer liquid surface and the ratio of the pore density of the inner liquid inlet surface to the outer liquid inlet surface are both within an ideal range.

[0073] At the same time, after the rapid initial phase separation, the raw membrane is immersed in the second coagulation bath for slow phase separation, and the phase separation time is 30-80s. The temperature of the second coagulation bath is not lower than the temperature of the casting liquid. The mass content of the fourth organic solvent is lower than the mass content of the third organic solvent in the first coagulation bath. As a result, the phase separation speed is slower than that in the rapid initial phase separation process. In addition, due to the small number of holes formed on the outflowing liquid surface in the rapid initial phase separation step, the phase separation speed is further slowed down, thereby forming a large pore area of ​​the sulfone polymer hollow fiber ultrafiltration membrane of the present invention.

[0074] Preferably, we also found in the study that when the temperature of the second coagulation bath is 10-45°C lower than the temperature of the first coagulation bath, due to the influence of factors such as the content of the fourth organic solvent in the second coagulation bath is much lower than the content of the third organic solvent in the first coagulation bath, the temperature difference between the second coagulation bath and the first coagulation bath and the temperature of the casting liquid, the phase separation rate of the membrane changes during the phase separation process, and a small pore area is formed between the large pore area and the outgoing liquid surface.

[0075] The green membrane obtained after phase separation is washed and dried in water to obtain a sulfone polymer hollow fiber ultrafiltration membrane. Preferably, the green membrane that is completely phase separated can be stretched, and the stretching treatment refers to a slight stretching of the green membrane by 1%-5%. After the green membrane is stretched, its mechanical strength will be improved, which can make the ultrafiltration membrane have better compressive strength. At the same time, the stretching ratio is small, which has little or no effect on the pore size of the membrane pores, ensuring that the final membrane still has a suitable pore size and excellent interception efficiency.

[0076] The third aspect of the present invention provides a sulfone polymer hollow fiber ultrafiltration membrane assembly, comprising the above-mentioned sulfone polymer hollow fiber ultrafiltration membrane and a cylindrical shell; the ultrafiltration membrane is located in the cylindrical shell, and the ultrafiltration membranes are bonded to each other through a colloid; the inner cavity diameter of the ultrafiltration membrane is 0.4-2.0mm.

[0077] The main process of preparing a hollow fiber membrane into a hollow fiber membrane assembly includes: (1) arranging multiple hollow fiber membrane fibers in parallel to form a membrane fiber bundle with flush ends; (2) using a pore plugging agent to plug the membrane fiber holes; (3) installing the membrane fiber bundle with blocked membrane fiber holes into a shell; (4) pouring a potting compound into both ends of the membrane fiber bundle to form a sealed end; (5) after the pouring is completed, curing at room temperature for a certain period of time to ensure that the potting compound is completely cured; (6) after the curing is completed, cutting off the parts of the membrane fiber bundle with the pore plugging agent at both ends to make the membrane fiber holes conductive, thereby forming the final hollow fiber assembly. From the above preparation process, it can be seen that the sealing process has an important influence on the quality of the prepared hollow fiber membrane components. Through continuous research, we have found that when sulfone polymers are used as the material of hollow fiber ultrafiltration membranes, their surface energy is not less than 60mN / m, while the surface energy of colloids is usually below 50mN / m. Since the surface energy of colloids is lower than that of sulfone polymers, it is conducive to the bonding between hollow fiber membranes made of sulfone polymers, and it is also convenient for colloids to enter the interior of the membranes relatively easily. At the same time, by controlling the pore density of the outgoing liquid surface to 20 / 25μm 2 -200 pieces / 25μm 2 , when the hollow fiber ultrafiltration membrane with the average SEM pore size of the first hole is 50nm-1000nm is made into an assembly, the colloid can partially penetrate into the membrane filaments, but will not enter too much into the membrane filaments to block the membrane pores or even the membrane cavity. If the colloid blocks the membrane pores seriously or blocks the membrane cavity, it will cause blockage of the liquid inlet, and the membrane filaments that are blocked by the colloid in the membrane pores or the membrane cavity must be cut off and the membrane filaments must be sealed again, resulting in waste of the membrane filaments. That is, under the synergistic effect of the average SEM pore size of the first hole and the pore density of the outgoing liquid surface, the bonding force between the membrane filaments is guaranteed, while the quality of the hollow fiber membrane assembly and the success rate of the preparation of the hollow fiber membrane assembly are improved, unnecessary waste is reduced, and membrane pollution can be reduced, which is suitable for the filtration of biological macromolecules.

[0078] The fourth aspect of the present invention provides an application of a sulfone polymer hollow fiber ultrafiltration membrane, which is used in the form of tangential flow for: (a) purification, concentration and dialysis of vaccines or viral vectors; (b) concentration and dialysis of proteins; (c) clarification and filtration of cells and bacteria in fermentation broth; (d) recovery and dialysis of cells and bacteria; (e) nucleic acid concentration; (f) preparation of pyrogen-free buffer; (g) extraction and purification of small molecule antibiotics to remove large molecular impurities; (h) removal of pyrogens from small molecule active substances / small molecule antibiotics; and (i) antibody concentration.

[0079] Compared with the prior art, the present invention has the following beneficial technical effects:

[0080] 1. The present invention scientifically regulates the SEM average pore size of the outgoing liquid surface of the sulfone polymer hollow fiber ultrafiltration membrane, the ratio of the SEM average pore size of the inlet liquid surface to the SEM average pore size of the outgoing liquid surface, and the range of the overall pore size and porosity of the ultrafiltration membrane. The prepared ultrafiltration membrane still ensures the flux of the ultrafiltration membrane when the outgoing liquid surface surface density is relatively low, overcomes the technical prejudice that the membrane flux is too low when the outgoing liquid surface surface density is relatively low, and at the same time obtains the excellent compressive strength of the membrane outgoing liquid surface, the excellent mechanical strength of the membrane as a whole, and the effect of reducing the risk of contamination of the outgoing liquid surface, which is more suitable for the needs of biological ultrafiltration.

[0081] 2. The present invention scientifically regulates the range of the SEM average pore size and the pore density of the outgoing liquid surface of the sulfone polymer hollow fiber ultrafiltration membrane, so that when the membrane filaments are used to prepare hollow fiber membrane modules, the membrane filaments have excellent bonding strength and reduce the contamination of the membrane filaments by colloids, thereby improving the quality of the hollow fiber modules and the success rate of the preparation of the hollow fiber modules, and at the same time being able to meet the requirements of biological ultrafiltration under harsh conditions.

[0082] 3. The sulfone polymer hollow fiber ultrafiltration membrane of the present invention is integrally formed by a casting liquid, and has the advantages of simple preparation method, better cost, green environmental protection, and suitability for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0083] Figure 1 This is a schematic scanning electron microscope (SEM) image of the outflowing liquid surface of the sulfone polymer hollow fiber ultrafiltration membrane prepared in Example 3, wherein the magnification is 5000×.

[0084] Figure 2 This is a schematic scanning electron microscope (SEM) image of a further magnified outflowing liquid surface of the sulfone polymer hollow fiber ultrafiltration membrane prepared in Example 3, wherein the magnification is 10000×.

[0085] Figure 3 This is a schematic scanning electron microscope (SEM) image of the liquid inlet surface of the sulfone polymer hollow fiber ultrafiltration membrane prepared in Example 3, wherein the magnification is 20000×.

[0086] Figure 4 This is a scanning electron microscope (SEM) schematic diagram of a further magnified liquid inlet surface of the sulfone polymer hollow fiber ultrafiltration membrane prepared in Example 3, wherein the magnification is 50000×.

[0087] Figure 5 This is a schematic scanning electron microscope (SEM) image of the entire sulfone polymer hollow fiber ultrafiltration membrane prepared in Example 3, where the magnification is 500×.

[0088] Figure 6This is a schematic diagram of a scanning electron microscope (SEM) of the sulfone polymer hollow fiber ultrafiltration membrane prepared in Example 3, close to the outgoing liquid surface, wherein the magnification is 2000×.

[0089] Figure 7 Schematic diagram of the test setup for interception efficiency and water flux testing. DETAILED DESCRIPTION

[0090] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0091] Example 1

[0092] A method for preparing a sulfone polymer hollow fiber ultrafiltration membrane comprises the following steps:

[0093] Step 1: Preparation of casting liquid and core liquid

[0094] The casting solution includes the following materials in parts by weight: 25 parts of bisphenol A polysulfone, 60 parts of dimethyl sulfoxide, 15 parts of polyethylene glycol and 3 parts of water, with a temperature of 25° C., a solid content of 24.30%, and a viscosity of 95,000 cps;

[0095] The core liquid includes dimethyl sulfoxide and water, and the mass content of dimethyl sulfoxide in the core liquid is 5%;

[0096] Step 2: Extruding the casting liquid and the core liquid together at the spinneret to form a molded product having an inner liquid inlet surface and an outer liquid outlet surface;

[0097] Step 3: First, perform preliminary phase separation on the molded product and immerse the molded product in the first coagulation bath at 50°C for 0.2s

[0098] forming a green film; wherein the first coagulation bath comprises dimethyl sulfoxide and water, and the mass content of dimethyl sulfoxide in the first coagulation bath is 60%;

[0099] Step 4: immersing the obtained raw film in a second coagulation bath at 30° C. for phase separation for 35 seconds, and stretching by 2%, wherein the second coagulation bath comprises dimethyl sulfoxide and water, and the mass content of dimethyl sulfoxide in the second coagulation bath is 5%;

[0100] Step 5: The membrane obtained by stretching in step 4 is washed with pure water and then dried to obtain a 5kD bisphenol A polysulfone hollow fiber ultrafiltration membrane, which has a membrane pore structure that first increases, then decreases, and then increases again in the direction from the inner liquid inlet surface to the outer liquid surface, that is, it has the structure of the large pore area and the small pore area described in the present invention.

[0101] Example 2

[0102] A method for preparing a sulfone polymer hollow fiber ultrafiltration membrane comprises the following steps:

[0103] Step 1: Preparation of casting liquid and core liquid

[0104] The casting solution includes the following materials by weight: 25 parts of polyethersulfone, 55 parts of dimethylacetamide, 20 parts of polyethylene glycol and 8 parts of water, with a temperature of 40° C., a solid content of 23.10%, and a viscosity of 93,000 cps;

[0105] The core liquid includes dimethylacetamide and water, and the mass content of dimethylacetamide in the core liquid is 8%;

[0106] Step 2: Extruding the casting liquid and the core liquid together at the spinneret to form a molded product having an inner liquid inlet surface and an outer liquid outlet surface;

[0107] Step 3: First, perform preliminary phase separation on the molded product and immerse the molded product in the first coagulation bath at 75°C for 0.4s.

[0108] forming a green film; wherein the first coagulation bath comprises dimethylacetamide and water, and the mass content of dimethylacetamide in the first coagulation bath is 75%;

[0109] Step 4: immersing the obtained raw film in a second coagulation bath at 50° C. for phase separation for 50 seconds, and stretching by 3%, wherein the second coagulation bath comprises dimethylacetamide and water, and the mass content of dimethylacetamide in the second coagulation bath is 10%;

[0110] Step 5: The membrane obtained by stretching in step 4 is washed with pure water and then dried to obtain a 10kD polyethersulfone hollow fiber ultrafiltration membrane, which has a membrane pore structure that first increases, then decreases, and then increases again in the direction from the inner liquid inlet surface to the outer liquid surface, that is, it has the structure of the large pore area and the small pore area described in the present invention.

[0111] Example 3

[0112] A method for preparing a sulfone polymer hollow fiber ultrafiltration membrane comprises the following steps:

[0113] Step 1: Preparation of casting liquid and core liquid

[0114] The casting solution comprises the following materials by weight: 20 parts of polyethersulfone, 50 parts of dimethylformamide, 18 parts of polyvinylpyrrolidone and 5 parts of water, with a temperature of 20° C., a solid content of 21.50%, and a viscosity of 82,000 cps;

[0115] The core liquid includes dimethylformamide and water, and the mass content of dimethylformamide in the core liquid is 15%;

[0116] Step 2: Extruding the casting liquid and the core liquid together at the spinneret to form a molded product having an inner liquid inlet surface and an outer liquid outlet surface;

[0117] Step 3: First, perform preliminary phase separation on the molded product and immerse the molded product in the first coagulation bath at 60°C for 0.8s

[0118] forming a green film; wherein the first coagulation bath comprises dimethylformamide and water, and the mass content of dimethylformamide in the first coagulation bath is 80%;

[0119] Step 4: immersing the obtained raw film in a second coagulation bath at 30° C. for phase separation for 55 seconds, and stretching by 3%, wherein the second coagulation bath comprises dimethylformamide and water, and the mass content of dimethylformamide in the second coagulation bath is 15%;

[0120] Step 5: The membrane obtained by stretching in step 4 is washed with pure water and then dried to obtain a 50kD polyethersulfone hollow fiber ultrafiltration membrane, which has a membrane pore structure that first increases, then decreases, and then increases again in the direction from the inner liquid inlet surface to the outer liquid surface, that is, it has the structure of the large pore area and the small pore area described in the present invention.

[0121] Example 4

[0122] A method for preparing a sulfone polymer hollow fiber ultrafiltration membrane comprises the following steps:

[0123] Step 1: Preparation of casting liquid and core liquid

[0124] The casting solution includes the following materials in parts by weight: 18 parts of polyethersulfone, 50 parts of N-methylpyrrolidone, 22 parts of polyvinyl alcohol and 4 parts of water, with a temperature of 25° C., a solid content of 19.15%, and a viscosity of 46,000 cps;

[0125] The core liquid comprises N-methylpyrrolidone and water, wherein the mass content of N-methylpyrrolidone in the core liquid is 20%;

[0126] Step 2: Extruding the casting liquid and the core liquid together at the spinneret to form a molded product having an inner liquid inlet surface and an outer liquid outlet surface;

[0127] Step 3: First, perform preliminary phase separation on the molded product and immerse the molded product in the first coagulation bath at 55°C for 1.0s

[0128] forming a raw film; wherein the first coagulation bath comprises N-methylpyrrolidone and water, and the mass content of N-methylpyrrolidone in the first coagulation bath is 90%;

[0129] Step 4: immersing the obtained raw film in a second coagulation bath at 35° C. for phase separation for 65 seconds, and stretching it by 5%, wherein the second coagulation bath comprises N-methylpyrrolidone and water, and the mass content of N-methylpyrrolidone in the second coagulation bath is 20%;

[0130] Step 5: The membrane obtained by stretching in step 4 is washed with pure water and then dried to obtain a 100kD polyethersulfone hollow fiber ultrafiltration membrane, which has a membrane pore structure that first increases, then decreases, and then increases again in the direction from the inner liquid surface to the outer liquid surface, that is, it has the structure of the large pore area and the small pore area described in the present invention.

[0131] The structure, overall porosity, overall tensile strength, overall elongation at break, surface energy and roughness of the membrane outflow liquid surface of the ultrafiltration membranes prepared in Examples 1 to 4 were characterized, and the specific results are as follows:

[0132] Table 1 - Overall characteristics of ultrafiltration membrane

[0133] sample Example 1 Example 2 Example 3 Example 4 Overall film thickness / μm 110 140 130 150 Overall membrane porosity / % 46.34 53.48 62.90 58.72 Tensile strength of the entire membrane / cN 162 186 170 219 Elongation at break of the entire film / % 36 72 57 100

[0134] Table 2 - Characteristics of outgoing liquid level and ingoing liquid level

[0135]

[0136]

[0137] Table 3 - Characteristics of the macroporous region

[0138]

[0139]

[0140] Table 4 - Characteristics of the small hole area

[0141]

[0142] Characterization of interception efficiency

[0143] The interception efficiency test method is as follows:

[0144] Step 1: Follow Figure 7 Connect the hollow fiber membrane assembly, pressure gauge, peristaltic pump, feed liquid container (containing the trapped substance), valve and receiving bottle in sequence to form a circulation system;

[0145] Step 2: Turn on the peristaltic pump and run at 6000s -1 Adjust the pump speed according to the shear rate to fill the pipeline with liquid and remove the air in the pipeline;

[0146] Step 3: Adjust the reflux valve so that the pressure gauge reading is between 8-16 psi. When the trapped material is about to drip out, press the stopwatch to start timing. Take a sample after 10 minutes and test its absorbance on a UV spectrophotometer, record it as A 透过 The absorbance of the original solution of the retained substance is recorded as A 原液 , its interception efficiency = 1-A 透过 / A 原液, The detailed results are shown in Table 5 below:

[0147] Table 5 - Retention efficiency of ultrafiltration membrane

[0148]

[0149] From the above results, it can be seen that the sulfone polymer hollow fiber ultrafiltration membranes prepared in Examples 1-4 have excellent retention efficiency.

[0150] Characterization of water flux

[0151] The test method for water flux is as follows:

[0152] Step 1: Follow Figure 7 Connect the hollow fiber membrane assembly, pressure gauge, peristaltic pump, liquid container (filled with purified water), valve and receiving bottle in sequence to form a circulation system;

[0153] Step 2: Adjust the transmembrane pressure to 5psi. After the permeate flow rate stabilizes for 3 minutes, collect the permeate in a beaker and press the stopwatch at the same time. Stop collecting the liquid after 1 minute, weigh and record the data. Repeat 3 times to calculate the average value. Measure the water temperature at the same time and convert it to the value of LMH / psi at 25°C according to the viscosity coefficient. This is the water flux of the membrane fiber. The results are shown in Table 6.

[0154] Table 6 - Water flux of ultrafiltration membrane

[0155]

[0156] From the above results, it can be seen that the sulfone polymer hollow fiber ultrafiltration prepared in Examples 1-4 all have excellent initial water flux, and the water flux after 10 complete uses is more than 80% of the initial water flux, and has good membrane stability and durability.

[0157] Example 5

[0158] A 50 kD polyethersulfone hollow fiber ultrafiltration membrane was prepared according to the preparation method of Example 3, except that the phase separation time in the first coagulation bath in step 3 was 1.1 s, the mass content of dimethylformamide in the first coagulation bath was 70%, and there was no stretching operation in step 4. The polyethersulfone hollow fiber ultrafiltration membrane finally obtained still had a structure with large pore areas and small pore areas, and the pore density of the outflowing liquid surface was 178 / 25 μm 2 The hole density of the inner liquid surface is 161 / 25μm 2The ratio of the pore density of the inner liquid inlet surface to the pore density of the outer liquid surface is 0.90. Compared with Example 3, the compressive strength of the outer liquid surface of Example 5 is relatively low, and its tensile strength is 153cN. In addition, the amount of colloid entering the membrane filaments during the assembly process of the membrane filaments is relatively large, which makes the overall membrane flux slightly low. The initial water flux is 34.62LMH / psi. At the same time, when the hollow fiber membrane assembly is prepared, the amount of colloid entering the membrane filaments is slightly large, but the inside of the membrane filaments is not completely blocked.

[0159] Example 6

[0160] A 50kD polyphenylsulfone hollow fiber ultrafiltration membrane was prepared by referring to the preparation method of Example 3, except that the composition of the casting solution in step one included the following material compositions in parts by mass: 22 parts of polyphenylsulfone, 50 parts of dimethylformamide, 30 parts of polyvinylpyrrolidone and 5 parts of water, the temperature was 20°C, the solid content was 20.56%, the viscosity was 79,000 cps, and there was no stretching operation in step four. The polyphenylsulfone hollow fiber ultrafiltration membrane finally obtained still had a structure with large pore areas and small pore areas, and the surface energy of the outgoing liquid surface was 95 mN / m. Compared with Example 3, the membrane filaments of Example 6 were more easily penetrated by the colloid during the assembly process, making the overall flux of the membrane slightly lower, and the initial water flux was 33.71 LMH / psi. At the same time, when the hollow fiber membrane assembly was prepared, the amount of colloid entering the interior of the membrane filaments was slightly more, but the interior of the membrane filaments was not completely blocked.

[0161] Example 7

[0162] A 50 kD polyethersulfone hollow fiber ultrafiltration membrane was prepared according to the preparation method of Example 3, except that the phase separation time in the first coagulation bath in step 3 was 0.5 s, the mass content of dimethylformamide in the first coagulation bath was 85%, and there was no stretching operation in step 4. The polyethersulfone hollow fiber ultrafiltration membrane finally obtained still had a structure with large pore areas and small pore areas, and the pore density of the outflowing liquid surface was 22 / 25 μm 2 Compared with Example 3, the membrane prepared in Example 7 has relatively fewer holes in the outflowing liquid surface, and the overall membrane flux is slightly lower, with an initial water flux of 32.85LMH / psi. At the same time, when prepared into a hollow fiber membrane assembly, the bonding force between the membrane filaments is slightly low.

[0163] Example 8

[0164] A 50kD polyethersulfone hollow fiber ultrafiltration membrane was prepared by referring to the preparation method of Example 3, with the difference that the temperature of the first coagulation bath in step three is 35°C, and the temperature of the second coagulation bath in step four is 65°C, the mass content of dimethylformamide in the second coagulation bath is 35%, and there is no stretching. The finally obtained polyethersulfone hollow fiber ultrafiltration membrane only has a structure of a large pore region, and the distance A from the large pore region to the outgoing liquid surface is 34 μm, and the thickness of the large pore region is 63 μm. Compared with Example 3, the overall structure of the membrane of Example 8 does not contain a small pore region, and its mechanical strength is slightly worse, and its tensile strength is 153 cN.

[0165] Example 9

[0166] A 50kD polyethersulfone hollow fiber ultrafiltration membrane was prepared by referring to the preparation method of Example 3, except that the mass content of dimethylformamide in the first coagulation bath in step three was 85%, the temperature was 25°C, and the temperature of the second coagulation bath in step four was 55°C and there was no stretching. The finally obtained polyethersulfone hollow fiber ultrafiltration membrane only had the structure of a large pore zone, and the distance A from the large pore zone to the outgoing liquid surface was 17 μm, and the thickness of the large pore zone was 80 μm. Compared with Example 3, the thickness of the large pore zone of the membrane prepared in Example 9 was thicker, and the distance A between the large pore zone and the outgoing liquid surface was relatively close. The compressive strength of the membrane at the outgoing liquid surface was relatively low, resulting in a slightly lower overall mechanical strength of the membrane, and its tensile strength was 135 cN.

[0167] Example 10

[0168] A 50kD polyethersulfone hollow fiber ultrafiltration membrane was prepared by referring to the preparation method of Example 3, except that the temperature of the first coagulation bath in step three was 35°C, and the temperature of the second coagulation bath in step four was 35°C, the organic solvent in the second coagulation bath was a mixed solvent of dimethylformamide (50% by mass) and dimethylacetamide (50% by mass), the mass content of the organic solvent was 5%, and there was no stretching. The finally obtained polyethersulfone hollow fiber ultrafiltration membrane had a structure with neither large pore areas nor small pore areas. Compared with Example 3, the membrane structure of Example 10 contained neither small pore areas nor large pore areas, and the overall flux of the membrane and the overall mechanical strength of the membrane were relatively low, with an initial water flux of 28.32LMH / psi and a tensile strength of 121cN.

[0169] Embodiment 11

[0170] Three of each of the sulfone polymer hollow fiber ultrafiltration membranes prepared in Examples 1-10 were prepared into a hollow fiber membrane assembly, in which the membrane filaments were bonded together by epoxy resin and then loaded into a cylindrical shell. The hollow fiber membrane assembly obtained by using the sulfone polymer hollow fiber ultrafiltration membrane prepared in Examples 1-4 had better bonding strength and water flux between the membrane filaments.

[0171] Comparative Example 1

[0172] A 50 kD polyethersulfone hollow fiber ultrafiltration membrane was prepared according to the preparation method of Example 3, except that the composition of the casting solution in step 1 includes the following mass parts: 18 parts of polyethersulfone, 50 parts of dimethylformamide, 30 parts of polyvinylpyrrolidone and 4 parts of water, the temperature is 20°C, the solid content is 17.64%, the viscosity is 39,000 cps, the time of the first coagulation bath in step 3 is 2s, and the mass content of dimethylformamide in the second coagulation bath in step 4 is 25% and there is no stretching operation. The pore density of the outgoing liquid surface of the finally obtained polyethersulfone hollow fiber ultrafiltration membrane is 245 pores / 25 μm 2 The hole density of the inner liquid surface is 183 / 25μm 2 That is, the number of holes on the outgoing liquid surface is much greater than the number of holes on the inner liquid surface, which makes the compressive strength of the outgoing liquid surface very low, and then leads to the low mechanical strength of the membrane as a whole. Its tensile strength is 86cN, which does not meet the needs of practical applications. At the same time, the colloid will enter the membrane filament too much, and the colloid will block the entire membrane filament and the liquid inlet, making it impossible to successfully prepare a usable hollow fiber membrane assembly.

[0173] Comparative Example 2

[0174] A 50 kD polyethersulfone hollow fiber ultrafiltration membrane was prepared by referring to the preparation method of Example 3, except that the rapid preliminary phase separation step 3 was omitted, and the mass content of dimethylformamide in the second coagulation bath in step 4 was 40%, the temperature of the second coagulation bath was 100°C, and there was no stretching operation. The pore density of the outflow liquid surface of the finally obtained polyethersulfone hollow fiber ultrafiltration membrane was 18 / 25 μm 2 The SEM average pore size of the first hole is 45nm, and its pore density and corresponding SEM average pore size are very small. The overall initial water flux of the membrane is 5.23LMH / psi, which cannot meet the requirements. Moreover, when processed into a hollow fiber membrane component, it is difficult for the colloid to enter the interior of the membrane fiber, resulting in insufficient bonding force, and it is impossible to obtain a qualified hollow fiber membrane component.

[0175] Comparative Example 3

[0176] A 50kD polyethersulfone hollow fiber ultrafiltration membrane was prepared by referring to the preparation method of Example 3, except that the composition of the casting solution in step 1 includes the following material compositions in parts by mass: 16 parts of polyethersulfone, 50 parts of dimethylformamide, 30 parts of polyvinylpyrrolidone and 4 parts of water, the temperature is 20°C, the solid content is 16.00%, the viscosity is 14,000 cps, and the temperature of the first coagulation bath in step 3 and the temperature of the second coagulation bath in step 4 are both 20°C, there is no stretching operation, and the SEM average pore size of the first hole on the outgoing liquid surface of the finally obtained polyethersulfone hollow fiber ultrafiltration membrane is 1100nm, and the overall porosity of the membrane is 82%, which is high, indicating that the number of membrane pores is too large, resulting in too low overall mechanical strength of the membrane, and its tensile strength is 74cN. At the same time, too much colloid enters the interior of the membrane filament, the colloid will block the entire interior of the membrane filament and the liquid inlet, and a usable hollow fiber membrane assembly cannot be successfully prepared.

[0177] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A sulfone polymer hollow fiber ultrafiltration membrane, comprising a main body, one side of the main body is an inner liquid inlet surface facing the inner cavity, the other side of the main body is an outgoing liquid surface, and the main body has a non-directional tortuous passage, characterized in that: The outgoing liquid surface comprises a plurality of first holes, the average pore size of the first holes by SEM is 50nm-1000nm, and the pore density of the outgoing liquid surface is 20 / 25μm. 2 -200 pieces / 25μm 2 ; The inner liquid inlet surface comprises a plurality of second holes, and the ratio of the SEM average pore size of the second holes to the SEM average pore size of the first holes is 1:2-10; The ratio of the pore density of the inner liquid inlet surface to the pore density of the outer liquid surface is 0.8-15; The overall porosity of the ultrafiltration membrane is 30%-80%.

2. The sulfone polymer hollow fiber ultrafiltration membrane according to claim 1, characterized in that: The average pore size of the second pores measured by SEM is 3 nm to 450 nm; The hole density of the inner liquid inlet surface is 30 / 25 μm 2 -800 pieces / 25μm 2 ; and / or, The ratio of the pore density of the inner liquid inlet surface to the pore density of the outer liquid surface is 1.1-10.

3. The sulfone polymer hollow fiber ultrafiltration membrane according to claim 1, characterized in that: The surface energy of the outflowing liquid surface of the ultrafiltration membrane is not less than 60mN / m, preferably 65mN / m-90mN / m; The roughness of the liquid outlet surface of the ultrafiltration membrane is 3 μm-50 μm, preferably 5 μm-35 μm; The average pore size of the first pores under SEM is 80nm-400nm, and the pore density of the outgoing liquid surface is 25 / 25μm. 2 -150 pieces / 25μm 2 .

4. The sulfone polymer hollow fiber ultrafiltration membrane according to claim 1, characterized in that: In the thickness direction from the inner liquid inlet surface to the outer liquid outlet surface, the average pore size of the main body increases first and then decreases; The main body includes a macroporous area, and the closest average distance A from the macroporous area to the outgoing liquid surface is not less than 15 μm; The average distance B between the macroporous area and the inner liquid surface is not less than 15 μm. The overall porosity of the ultrafiltration membrane is 35%-70%.

5. The sulfone polymer hollow fiber ultrafiltration membrane according to claim 4, characterized in that: The thickness of the macroporous region is 40 μm-120 μm; The ratio of the thickness of the macroporous region to the overall thickness of the membrane is 0.25-0.6; and / or, The ratio of the SEM average pore size of the macropore area to the SEM average pore size of the first pores is 3-20.

6. The sulfone polymer hollow fiber ultrafiltration membrane according to claim 4, characterized in that: The average distance A from the macroporous region to the outgoing liquid surface is 20 μm-60 μm, and the ratio of the distance A to the membrane thickness is 0.1-0.5; and / or, The ratio of the closest average distance A from the macroporous area to the outgoing liquid surface to the closest average distance B from the macroporous area to the inner inlet liquid surface is 0.6-2.

5.

7. The sulfone polymer hollow fiber ultrafiltration membrane according to claim 4, characterized in that: The macroporous region has a first cross-section fiber forming a porous structure, and the SEM average diameter of the first cross-section fiber is 20nm-180nm; and / or, The ratio of the SEM average pore size of the macroporous region to the SEM average diameter of the first cross-section fiber is 5-30.

8. The sulfone polymer hollow fiber ultrafiltration membrane according to claim 4, characterized in that: In the thickness direction from the inner liquid inlet surface to the outer liquid surface, the average pore size of the main body increases first, then decreases, and then increases again, and the main body includes a small pore area, and the small pore area is located between the large pore area and the outer liquid surface. The average distance C between the small hole area and the outgoing liquid surface is not less than 2 μm; The overall porosity of the ultrafiltration membrane is 40%-65%.

9. The sulfone polymer hollow fiber ultrafiltration membrane according to claim 8, characterized in that: The thickness of the pinhole area is 5 μm-30 μm; The ratio of the thickness of the small hole area to the overall thickness of the membrane is 0.05-0.15; and / or, The ratio of the thickness of the small pore area to the thickness of the large pore area is 0.1-0.

4.

10. The sulfone polymer hollow fiber ultrafiltration membrane according to claim 8, characterized in that: The SEM average pore size of the small pore area is 0.1-0.4 of the SEM average pore size of the large pore area. and / or, The small hole area has a second cross-section fiber that forms a porous structure, and the SEM average diameter of the second cross-section fiber is 10nm-150nm.

11. The sulfone polymer hollow fiber ultrafiltration membrane according to claim 8, characterized in that: The average distance C between the pinhole area and the outgoing liquid surface is 4 μm-20 μm; the ratio of the distance C to the membrane thickness is 0.04-0.1; and / or, The ratio of the closest average distance C from the small hole area to the outgoing liquid surface to the closest average distance A from the large hole area to the outgoing liquid surface is 1:2-15.

12. The sulfone polymer hollow fiber ultrafiltration membrane according to claim 1, characterized in that : The initial water flux of the ultrafiltration membrane is 0.5LMH / psi-300LMH / psi, preferably 1LMH / psi-250LMH / psi; The water flux of the ultrafiltration membrane after 10 complete uses is more than 70% of the initial water flux; The tensile strength of the ultrafiltration membrane is 100 cN-350 cN, preferably 160 cN-280 cN, and the elongation at break is not less than 15%, preferably 20%-150%; The film thickness is 90 μm-200 μm.

13. A method for preparing a sulfone polymer hollow fiber ultrafiltration membrane according to any one of claims 1 to 12, characterized in that: The steps include: Step 1: Prepare casting liquid and core liquid: The casting solution comprises a sulfone polymer, a first organic solvent, a hydrophilic additive and a non-solvent; the solid content of the sulfone polymer in the casting solution is 15%-25%, and the viscosity of the casting solution is 10,000-100,000 cps; The core liquid comprises a second organic solvent and water, wherein the mass content of the second organic solvent in the core liquid is 0-40%; Step 2: Spinning: The casting liquid and the core liquid prepared in step 1 are extruded from the spinneret together to form a molded product having an inner liquid surface and an outer liquid surface, wherein the temperature of the casting liquid is 20-40° C.; Step 3: Rapid preliminary phase separation: immersing the molded product obtained in step 2 into a first coagulation bath for rapid phase separation, the phase separation time is 0.1-1.2s, the temperature of the first coagulation bath is 5-50°C higher than the temperature of the casting solution, to form a green film; wherein the first coagulation bath contains water and a third organic solvent, and the mass content of the third organic solvent is greater than 50%; Step 4: Complete phase separation: immersing the raw film obtained in step 3 into a second coagulation bath for complete phase separation, wherein the phase separation time is 30-80s, and the temperature of the second coagulation bath is not lower than the temperature of the casting solution; wherein the second coagulation bath contains water and a fourth organic solvent, and the mass content of the fourth organic solvent is not more than 30%; Step 5: Cleaning and drying: The raw membrane obtained in step 4 is cleaned with pure water and then dried to obtain a sulfone polymer hollow fiber ultrafiltration membrane.

14. The method for preparing a sulfone polymer hollow fiber ultrafiltration membrane according to claim 13, characterized in that: The sulfone polymer is at least one of bisphenol A polysulfone, polyethersulfone, polyphenylsulfone and sulfonated polyethersulfone; The first organic solvent, the second organic solvent, the third organic solvent and the fourth organic solvent are at least one of dimethylformamide, dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide; The hydrophilic additive is at least one of polyethylene glycol, polyvinyl pyrrolidone and polyvinyl alcohol; The non-solvent is at least one of water, isopropanol, glycerol and butanediol.

15. The method for preparing a sulfone polymer hollow fiber ultrafiltration membrane according to claim 13, characterized in that: The mass content of the non-solvent in the casting solution is 1%-10%; and / or, The mass content of the third organic solvent in the first coagulation bath is 55%-95%; and / or, The mass content of the fourth organic solvent in the second coagulation bath is 0-25%.

16. The method for preparing a sulfone polymer hollow fiber ultrafiltration membrane according to claim 13, characterized in that: The temperature of the first coagulation bath is 30-50°C higher than the temperature of the casting solution; and / or, The temperature of the second coagulation bath is 10-45° C. lower than the temperature of the first coagulation bath; and / or, Step 4: When the phase separation is complete, the raw film is stretched with a stretching rate of 1%-5%.

17. A sulfone polymer hollow fiber ultrafiltration membrane module, characterized in that: Comprising the sulfone polymer hollow fiber ultrafiltration membrane according to any one of claims 1 to 12 and a cylindrical shell; The ultrafiltration membrane is located in the cylindrical housing, and the ultrafiltration membranes are bonded to each other through colloid; The inner cavity diameter of the ultrafiltration membrane is 0.4-2.0 mm.

18. Use of the sulfone polymer hollow fiber ultrafiltration membrane according to any one of claims 1 to 12, characterized in that: The ultrafiltration membrane is used in the form of tangential flow: (a) Purification, concentration and dialysis of vaccines or viral vectors; (b) protein concentration and dialysis; (c) clarification and filtration of cells and bacteria in fermentation broth; (d) Recovery and dialysis of cells and bacteria; (e) nucleic acid concentration; (f) Preparation of pyrogen-free buffer; (g) Extraction and purification of small antibiotic molecules to remove large molecular impurities; (h) Small molecule active substances / small molecule antibiotics to remove pyrogens; (i) Antibody concentration.

Citation Information

Patent Citations

  • Plasma purifying membrane and plasma purifying system

    CN1684727A

  • Polyether sulfone hollow fiber ultrafiltration membrane as well as preparation method and application thereof

    CN117797643A

  • Hollow fiber filter membrane as well as preparation method and application thereof

    CN117815909A

  • Polysulfone-based hollow yarn membrane and its preparation

    JP1990251233A

  • Polysulfone selectively permeable hollow fiber membrane

    JP2005348785A

Cited By

  • A polysulfone hollow filter membrane, a preparation method and application thereof

    CN122806344A